(untitled) (Fiep Bulletin - online, 2011)
From the antiquity, the physical activity has prescribed in the treatment and prevention of several illnesses. In the modern world, some studies show the importance of the physical activity in the conditions of the aged health. We know that the lifestyle is one of the factors that cause disease in the current society, owed mainly to the sedentary life and unhealthy life habits in the feeding; therefore, the physical activity becomes indispensable to avoid several illnesses that cause disability and precocious death. The measured that the people increase their levels of physical conditioning, they move forward towards a better quality of life with full accomplishment social, psychic, spiritual and labored, surpassing the stress and the depression. The life activates represents economy, reducing futures medical expenses, decreasing responsibilities to the family and the society. The physical activity to regulate it serves as a strategy of positive health, an amusement amid the lifestyle disturbed that the human beings take in the technological world of the present time, where the home, the family and the personal values are in an inferiority plan.